التحليل العملياتي للحركة المرورية باستخدام موديلات النمذجة الميكروسكوبية - تقييم وتحليل مركز مدينة طرطوس- - رستم, أكرم; قبع, عبد الرحمن (Latakia University Journal -Engineering Sciences Series, 2018)
تختلف أدوات التقييم والتحليل العملياتي من بلد إلى أخر، حيث لعبت ثورة تقنية المعلومات والتكنولوجيا في العقدين الماضيين دوراً هاماً في تغيير أدوات التحليل والتقييم للحركة المرورية، في هذه الدراسة تم استخدام نوع من أنواع الموديلات الميكروسكوبية (موديل Gipps) في التحليل العملياتي وبالاستعانة ببرنامج Simtraffic، وبنفس الوقت قمنا بالتحليل العملياتي باستخدام HCM2010، وبالاستعانة ببرنامج Synchro 9، حيث اعتمدنا في التحليل العملياتي وفق موديل Gipps على غزارات الإشباع والسرعة والفواصل الزمنية، وتم الاعتماد على أزمنة التأخير في تقييم أداء الشبكة المدروسة، وبالنسبة للتحليل العملياتي باستخدام HCM2010 تم الاعتماد على منهجية الكود المستخدمة من حيث متطلبات الإدخال، وأخذنا أزمنة التأخير كمؤشر أساسي لقياس أداء الشبكة المدروسة، ومن خلال مقارنة أزمنة التأخير والسرعة الفعلية فإن عمليات التقييم وفق الموديلين تعطي تصوراً واقعياً لمستويات الخدمة للشبكة المدروسة، وبالتالي يجب الأخذ بعين الإعتبار كلا الموديلين أثناء التحليل العملياتي. The tools of evaluation and operational analyze for traffic flow are changeable from each other. Every country has its own model. The technology revolution has change these tools. In this paper, we use one of the famous model in traffic analyze field. The Gipps Model, which known by the application of Traffic Ware Collection (Synchro- Simtraffic). We use Synchro 9.0 for the operational analyze depending on the High Way Capacity Manuel 2010 (HCM 2010) mythology. Then we use the Gipps model to evaluate the study area depending on microscopic criteria, which are Saturation flow, speed, headway and delay. After the operational analyze and microscopic evaluation, we choose two parameters to compare and estimate the performance of the network. Speed and Delay are the main parameters of comparison. According to speed and delay parameters, we determined the Level of Service (LOS) and a reflection of the field traffic flow. According to these promising results, we recommended analyzer to use both model in the operational analyze and evaluation of traffic flow.